THE EFFECTS OF DIVORCE ON THE PARTIES WITHIN Faculty of Law of Surakarta University - GUNAWAN GUNAWAN (RECHTSTAAT, 2014)
Abstract: The effect of divorce on husband-wife is that former husband and wife has lost their status after divorce, becoming widow and widower. The effect of divorce on children is that the children will feel confused, anxious, restless, shy, sad, and frequently have resentment and aversion, so that they become disorganized and wild. The effect of divorce on wealth is the presence of mutual wealth sharing.The research method employed was the descriptive one. As a prescriptive research, this current research studied legal objective, justice value, rule of law validity, legal concepts and legal norms. This descriptive research aimed to describe systematically a certain population or area. The descriptive research was intended to provide prior data as thorough as possible about human, condition or other phenomenon. The qualitative data analysis was a research method providing descriptive data in which what the respondents say in either written or spoken form and what they do actually were investigated and studied as something intact.It could be concluded that the reality was as same as the theory, in which mothers are entitled to educate their children and when the children had understood more, they could choose with whom they will live. Wealth is a very risky thing in the term of division (sharing). It is because justice is difficult to achieve in property sharing. For that reason, the courts or those authorized can conduct property sharing corresponding to respective party's desire or agreement, and mutual benefit. Thus, it will not result in dissension between the couple family. It means that despite divorce, they still establish a good relationship. Keywords: Divorce Effect, the Parties Within Divorce